Analisis Pengaruh Pendapatan Asli Daerah (PAD), Dana Alokasi Uumum (DAU) dan Inflasi Terhadap Pertumbuhan Ekonomi di Kabupaten/Kota Propinsi Jawa Tengah - Zuwesty Eka Putri (Faculty of Economic and Business, 2015)
This research was aimed to analyze the effect of own-source revenue, general allocation grant, and inflation to economic growth in distric or urban Province of Central Java from 2011 to 2014. This research used secondary data which collected from Statistic Indonesia (BPS) of Central Java. The research uses multiple regression analysis method The result of this research show that: (1) own-source revenue has significant influence on economic growth in distric or urban Province of Central Java. (2) general allocation grant has no significant effect on economic growth distric or urban Province of Central Java. (3) Inflation has no significant effect on economic growth distric or urban Province of Central Java distric or urban Province of Central Java. (4) own-source revenue, general allocation grant, and inflation together (simultaneously) has significant influence on the economic growth in the district or urban of Central Java.DOI: 10.15408/ess.v5i2.2340